2010
DOI: 10.1007/s00430-010-0159-9
|View full text |Cite
|
Sign up to set email alerts
|

Hidden hazards of HCV transmission

Abstract: Hepatitis C virus infection is a global health problem that has important epidemiological and clinical consequences. It has been well established that exposure to infected blood is the main risk factor for HCV transmission. However, in 20% of cases the agent transmission occurs by unknown route or in the presence of an unidentified source of infection. Understanding of the epidemiology of HCV is needed to help us define future control and preventive strategies. Herein, we discuss about diagnosis of HCV infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 48 publications
0
18
1
Order By: Relevance
“…Likewise another study was conducted in Egypt found each patient had at least three risk factors for getting HCV [15]. Our findings are inconsistent with the findings of a study revealed that in 20% of patients the agent transmission happened by unknown route [22].…”
Section: Risk Factors Scores Of Patients Regarding Hepatitis Ccontrasting
confidence: 99%
“…Likewise another study was conducted in Egypt found each patient had at least three risk factors for getting HCV [15]. Our findings are inconsistent with the findings of a study revealed that in 20% of patients the agent transmission happened by unknown route [22].…”
Section: Risk Factors Scores Of Patients Regarding Hepatitis Ccontrasting
confidence: 99%
“…However, the route of virus transmission cannot be clearly identifi ed in a considerable percentage of cases 7,8 .…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of screening strategies for HCV following its discovery in 1989 (Choo et al, 1989) has greatly reduced the transmission of the virus through blood transfusion and blood products, and the main transmission route of HCV in developed countries is now the use of contaminated needles by injecting drug users (Pondé, 2011). In developing countries, non-sterile injections and other unsafe medical interventions are thought to contribute to continuing HCV incidence (Kane et al, 1999).…”
Section: Introductionmentioning
confidence: 99%